Impact of Socio-economic Factors on the Perception of Equality of Opportunity - Krishna Bahadur G.C. (Tribhuvan Journal, 2024)
This article examines the various sociological and philosophical perspectives on equality of opportunity, focusing on areas of misunderstanding within these viewpoints. It aims to critically analyze these perspectives, highlighting the underlying assumptions and challenging simplistic approaches to the concept of equal opportunity. The article claims that these perspectives differ in knowledge, beliefs about the familiar world, and human comprehension. By critiquing the constitutionalist approach, which prioritizes overall quality of life, and contrasting it with the Marxist perspective, which emphasizes protection based on socioeconomic status, this essay challenges conventional notions of equal opportunity. It advocates for a perspective rooted in fundamental equality and social democratic philosophy, arguing against discrimination based on sex, gender, race, ethnicity, or socioeconomic status. The article posits that we should regard all individuals as equally valuable human beings. Furthermore, this study contends that the perception of equal opportunity remains misleading, as the most effective criteria for achieving it remain unresolved in specific contexts and situations. By examining these complexities, the article aims to contribute to a more nuanced understanding of equality of opportunity in contemporary society.